Identification and Simulation of Dc-Dc Boost Converter for Charging Up PV Voltage for 24-Volts Battery - Khamis, Aziah; Kamarudin, Muhammad Nizam (2010)
This manuscript is a piece of report on the identification of a DC-DC Boost switched mode converter for charging up Photovoltaic (PV) voltage for 24-volts battery. A DC-DC Boost converter with unknown mathematical characteristic is identified using Auto-Regressive with Exogenous Input (ARX) model. The identification of such DC-DC converter, on the basis of recorded data from PV is conducted to obtain the mathematical model of the converter. The knowledge about the converter is then beneficial for the design process of a PV’s maximum power point tracking (MPPT) system. The identification process that exploits the advantage of linear parametric ARX gives beneficial information such as correlation, best fit and poles-zeros location. The purpose of identification is to obtain the best model of the converter and hence, beneficial the simulation and controller design phase which include the MPPT.